1967
DOI: 10.1136/thx.22.6.519
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged treatment of pulmonary sarcoidosis with corticosteroids

Abstract: The results are described of prolonged corticosteroid treatment in 52 patients with pulmonary sarcoidosis observed for a mean duration of 10-5 years from diagnosis. Twenty of the patients -were treated for less than one year, the remainder for a mean of five years. The mean length of observation after discontinuing treatment was 5*5 years. Selection of patients for treatment was based on (1) evidence from radiographic observation, even for two years or more, that the disease was progressive so that spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Subsequent reports of uncontrolled series of patients treated for longer periods with oral corticosteroids, usually prednisone or prednisolone, generally confirmed these early findings Hoyle et al, 1955 ;Rudberg-Roos and Roos, 1958;James and Thomson, 1959;Scadding, 1961;Hoyle et al, 1967;Turaif et al, 1967;Johns and Ball, 1967;Barber et al, 1971;Refvem, 1974;johns et al, 1976;Middleton and Douglas, 1980b;Refvem and Refvem, 1980) . Extrathoraeie manifestations accessible to inspection are usually partially or completely suppressed.…”
Section: Corticosteroidsmentioning
confidence: 80%
“…Subsequent reports of uncontrolled series of patients treated for longer periods with oral corticosteroids, usually prednisone or prednisolone, generally confirmed these early findings Hoyle et al, 1955 ;Rudberg-Roos and Roos, 1958;James and Thomson, 1959;Scadding, 1961;Hoyle et al, 1967;Turaif et al, 1967;Johns and Ball, 1967;Barber et al, 1971;Refvem, 1974;johns et al, 1976;Middleton and Douglas, 1980b;Refvem and Refvem, 1980) . Extrathoraeie manifestations accessible to inspection are usually partially or completely suppressed.…”
Section: Corticosteroidsmentioning
confidence: 80%
“…Most authors agree that short-term benefits of corticosteroids are seen in most patients receiving them [7,[31][32][33][34]. With respect to the long-term benefits of corticosteroids, several prospective studies have suggested that temporary improvement may occur with the use of corticosteroids, but may not ultimately influence outcome, whereas others have demonstrated some long-term benefit to the use of steroids [6,9,30,[35][36][37][38][39]. However, recent meta-analyses have concluded that although chest X-ray, symptoms and spirometry appear to improve over time with corticosteroid use, data indicating a modifying effect on long-term disease progression are limited [7].…”
Section: Corticosteroidsmentioning
confidence: 98%
“…Where the illness has lasted for more than 3 years the chance of spontaneous remission is small. In such cases the glucocorticoids may inhibit progression and occasionally also improve the condition (15,27). It is interesting that a double-blind investigation using prednisone and oxyphenylbutazone revealed that the oxyphenylbutazone exhibited the same beneficial effect as prednisone (16).…”
Section: Some Workers Include This Disease Among the Connective Tissumentioning
confidence: 99%